(3TQM OjhGf GHf GdaGQVs - (3HOQ GdOjf MSf Hf eMeO Hf eMeO GdHhQjfi GdOeTbj GdTGaYjs; (3YeQ Hf Ydj Hf GdaGQV GdMehj, CHh MaU,J (B576 (3g` s ((3UfYGA s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY GdCOH hCgdg hHYO aEf GdWHY GdSdje GdPi jbOQ Ydi fXe GdTYQ GdehRhf WHY eTQa HGdPGJ Cf CYdb Ydi GdOjhGf GdePchQ TQMkG jHjf eG CTcd ef eYGfjg s
(3BNQgG (B:s
(3hgPG TCf ef cGf UGObkG , jLYd YOhg dg eUGObkG , hGdMeO ddg hMOg s
(3cJHJ GdCHjGJ ajgG HGdMeQIs
(3hYdjgG JedcGJ CbOegG SfI (B1170(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs